Communication Strategies Used by EFL Students with High and Low Self-Esteem - Rahmi Aulia Nurdini (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2017)
This study aimed to investigate communication strategies (CSs) used by EFL students with low and high self-esteem in speaking English. Methods employed were questionnaire, observation, and interview. Findings showed that students with low self-esteem employed fewer CSs compared to those with high self-esteem. Students with low self-esteem only used the strategies such as non-linguistic means, appeal for help, and fillers or hesitation device, while the students with high self-esteem level used six kinds of communication strategies such as message abandonment, non-linguistic means, literal translation, code switching, appeal for help, and fillers or hesitation device. The study suggests that EFL practitioners pay attention to self-esteem aspect to obtain the optimum results of teaching-learning processes.